1987
DOI: 10.1177/014662168701100207
|View full text |Cite
|
Sign up to set email alerts
|

Component Latent Trait Models for Paragraph Comprehension Tests

Abstract: The cognitive characteristics of paragraph comprehension items were studied by comparing models that deal with two general processing stages: text representation and response decision. The models that were compared included the prepositional structure of the text (Kintsch & van Dijk, 1978), various counts of surface structure variables and word frequency (Drum et al., 1981), a taxonomy of levels of text questions (Anderson, 1972), and some new models that combine features of these models. Calibrations from the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
167
2
5

Year Published

1989
1989
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 110 publications
(180 citation statements)
references
References 19 publications
6
167
2
5
Order By: Relevance
“…More specifically, DA focuses on the evaluation process as well as the product. It attempts to modify the student's performance during testing by introducing material or instructions to elicit higher achievement levels (Embretson & Wetzel, 1987).…”
Section: Literature Reviewmentioning
confidence: 99%
“…More specifically, DA focuses on the evaluation process as well as the product. It attempts to modify the student's performance during testing by introducing material or instructions to elicit higher achievement levels (Embretson & Wetzel, 1987).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Only a few studies appear to have focused on predicting item difficulty using items from standardized ability tests (Drum, Calfee, & Cook, 1981;Embretson & Wetzel, 1987). While not specifically focused on predicting reading item difficulty, many other studies of language processing have isolated a wide variety of variables that influence comprehension difficulty with respect to decision time and recall measures.…”
Section: Background Studiesmentioning
confidence: 99%
“…They reported good predictability using these simple surface variables; on average, they indicated that about 70% of the variance 1 of multiple-choice reading item difficulty was explained. Embretson and Wetzel (1987) also studied the predictability of 75 reading item difficulties using a few of the surface variables studied by Drum et al (1981). But in addition, because of the brevity of their passages, Embretson and Wetzel were able to do a propositional analysis (see Kintsch & van Dijk, 1978) and add variables from this analysis, along with several other measures, as predictor variables.…”
Section: Background Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Secondly, different problem attributes have differential effects on students' strategies and errors. Thus, construct validity problems might arise when examinees are tested on different sets of problems, as in computer adaptive testing (Embretson & Wetzel, 1987). If one examinee receives problems that are difficult because of the need to formulate an algebraic representation while another examinee is tested on problems that are difficult because of structural complexity, the same abilities may not be brought to bear by both examinees.…”
mentioning
confidence: 99%